2016
DOI: 10.3389/fped.2016.00062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yoga-Based Personality Development Program on Psychomotor Performance and Self-efficacy in School Children

Abstract: Selective attention and efficacy are important components of scholastic performance in school children. While attempts are being made to introduce new methods to improve academic performance either as part of curricular or extracurricular activities in schools, the success rates are minimal. Hence, this study assessed the effect of yoga-based intervention on psychomotor performance and self-efficacy in school children. Two hundred ten school children with ages ranging from 11 to 16 years (mean age ± SD; 13.7 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…This study results differ from those of studies on yoga that have used small study populations. [47] Many other studies have found yoga practices to be more effective than physical exercises in many physiological functions such as in muscle control, balance, increased self-confidence, and other measures that are not studied in this trial. [89]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study results differ from those of studies on yoga that have used small study populations. [47] Many other studies have found yoga practices to be more effective than physical exercises in many physiological functions such as in muscle control, balance, increased self-confidence, and other measures that are not studied in this trial. [89]…”
Section: Discussionmentioning
confidence: 99%
“…An integrated approach to yoga is necessary for the holistic development of memory,[3] attention, executive functioning, and cognitive processing speed. [4] Few studies that have directly compared the effects of participating in school-based yoga versus physical education have generally found positive effects of yoga. [5] Few studies have found that yoga is as effective as physical activity (PA) in improving cognitive performance and emotional and behavioral functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Yoga Personality Development camp has the significant effect on Satva, Rajas and Tamas in Children 18 . Results suggest that yoga practice enhances selfefficacy and processing speed with fine motor coordination, visual-motor integration, visual perception, planning ability, and cognitive performance 19 . In all the above references, there was no mention of standardization of scale development for the yoga concept of personal observance (niyama).…”
mentioning
confidence: 90%
“…Given the fact that the RT testing and the CFFF evaluation can measure information processing speed, attention, concentration and alertness [ 11 , 13 , 16 , 17 ], all of which are important factors presumed to be associated with higher academic achievement [ 24 – 26 ], it can be expected that better cognitive functions may also be linked with better academic performance [ 27 ]. There are very few studies that have explored this relationship, and although they have shown that there is a statistically significant relationship between faster RT and better academic performance, the correlation appears to be weak at best ( r = 0.07 to r = 0.29) [ 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%